Assessing safety and health factors influencing performance of Malaysian low-cost housing - Ramli, Azuin; Abidin Akasah, Zainal Abidin; Mohd Masirin, Mohd Idrus (2013)
The Malaysian Government through its various Malaysia Plans is committed to provide adequate, affordable, and quality low-cost housing in fulfilling nation’s housing need. Therefore, the housing policy should provide the public to own affordable housing that should improve the safety and health of a building’s final occupants. To achieve this aim, the information concerning the safety and health performance of buildings must always be readily available. The research first identified the critical factors through a literature review of current safety and health practices from journals, thesis and articles books in order to interpret the factors from a global perspective. The literature review identified 32 variables of factors contributing to safety and health performance of low cost housing in Malaysia. The findings of this study can form a basis that can be considered as primary elements for the development of practical assessment scheme to evaluate the safety and health of low-cost housing in Malaysia.